Phytochemical screening of three medicinally important epiphytic orchids of Bangladesh - Marjoka, A; Alam, O; Huda, MK (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not available Jahangirnagar University J. Biol. Sci. 5(1): 95-99, 2016 (June)